Efficacy of vinegar, sorbitol and sodium benzoate in mitigation of Salmonella contamination in betel leaf - Al Asmaul Husna; Md. Ariful Islam; Md. Tanvir Rahman; Mst. Minara Khatun (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was undertaken to mitigate Salmonella from betel leaf in Mymensingh. A total of 35 betel leaf samples were collected from 2 baroujes and 5 local markets in Mymensingh. The samples were sub-divided into two groups: (i) phosphate buffer solution (PBS) washed, and (ii) grinded sample. There was control and treated (with 1.5% vinegar, sorbitol, and sodium benzoate) sub-groups in both groups. Mitigation of Salmonella was determined by comparing Total Viable Count (TVC) and Total Salmonella Count (TSAC) of control with treated groups. No bacterial growth was observed in the betel leaf samples collected directly from barouj level. At market level, when grinded, there was no growth of bacteria in Plate Count Agar (PCA) and Salmonella- Shigella (SS) or Xylose Lysine De-oxy-chocolate (XLD) in both treated and untreated groups. But when the PBS washed samples were used, the TVC (mean log CFU±SD/mL) of betel leaf ranged from 5.16±0.82 to 5.96±1.11, whereas the TSAC value ranged from 4.87±0.58 to 5.56±1.00 for untreated group. In vinegar, there was no growth, but when treated with sorbitol, the TVC (mean log CFU±SD/mL) value reduced to 5.00±0.54 to 5.66±1.09, and TSAC (mean log CFU±SD/mL) value reduced to 4.28±0.71 to 4.78±0.64. When treated with sodium benzoate, the TVC (mean log CFU±SD/mL) value reduced to 5.06±0.53 to 5.75±1.02, and TSAC (mean log CFU±SD/mL) value reduced to 4.34±0.79 to 4.92±0.64. Data of this study indicates that all the three chemicals were effective in terms of reducing bacterial load but vinegar (1.5%) was found to be the most effective against Salmonella as well as some other bacteria when treated for 10 min.